Association of Clubroot Resistance Locus PbBa8.1 With a Linkage Drag of High Erucic Acid Content in the Seed of the European Turnip - Zhan, Zongxiang; Jiang, Yingfen; Shah, Nadil; Hou, Zhaoke; Zhou, Yuanwei; Dun, Bicheng; Li, Shisheng; Zhu, Li; Li, Zaiyun; Piao, Zhongyun; Zhang, Chunyu (Frontiers in Plant Science, 2020)
Clubroot disease caused by Plasmodiophora brassicae is a severe threat to the production of Brassica napus, worldwide. The cultivation of resistant varieties is the most efficient and environmentally friendly way to limit disease spread. We developed a highly resistant B. napus line, ZHE226, containing the resistance locus PbBa8.1. However, ZHE226 seeds contain high erucic acid content, which limits its cultivation owing to its low edible oil quality. A segregation population of BC3F2 was developed by crossing ECD04, a resistant European turnip donor, with Huangshuang5, an elite variety with no erucic acid in its seeds, as a recurrent plant. Fine mapping using the bulk segregation analysis sequencing (BSA-Seq) approach detected PbBa8.1within a 2.9 MB region on chromosome A08. Interestingly, the previously reported resistance gene Crr1a was found in the same region. Genetic analysis revealed that the CAP-134 marker for Crr1a was closely linked with clubroot resistance. Thus, PbBa8.1 and Crr1a might be allelic for clubroot resistance. Moreover, comparative and genetic analysis showed that high erucic acid in the seeds of ZHE226 was due to linkage drag of fatty acid elongase 1 (FAE1) in the ECD04 line, which was located in the interval of PbBa8.1 with a physical and genetic distance of 729 Kb and 1.86 cM, respectively. Finally, a clubroot-resistant line with a low erucic acid content was successfully developed through gene-specific molecular marker assistant selection from BC4F4. These results will accelerate clubroot resistance (CR) breeding programs in B. napus.